Forensic Facial Reconstruction: Relationship Between the Alar Cartilage and Piriform Aperture1. Issue 6 (29th March 2017) - Strapasson, Raíssa Ananda Paim; Herrera, Lara Maria; Melani, Rodolfo Francisco Haltenhoff
Abstract: During forensic facial reconstruction, facial features may be predicted based on the parameters of the skull. This study evaluated the relationships between alar cartilage and piriform aperture and nose morphology and facial typology. Ninety‐six cone beam computed tomography images of Brazilian subjects (49 males and 47 females) were used in this study. OsiriX software was used to perform the following measurements: nasal width, distance between alar base insertion points, lower width of the piriform aperture, and upper width of the piriform aperture. Nasal width was associated with the lower width of the piriform aperture, sex, skeletal vertical pattern of the face, and age. The current study contributes to the improvement of forensic facial guides by identifying the relationships between the alar cartilages and characteristics of the biological profile of members of a population that has been little studied thus far.